Analysis of the Effect of School Organizational Culture and Professional Learning Communities on Teacher Efficacy - Suk Yeol Lee (National Research Mordova State University, 2020)
Introduction. The aim of the study is to find ways to expand teacher efficacy by examining how the teacher's efficacy varies according to the school organisation culture and the level of the professional learning community. Materials and Methods. Survey methods were used to collect the data from 400 in-service teachers at elementary, middle, and high schools in South Korea, with five schools selected from each region, respectively. This study utilizes the data from 359 teachers. This study used a random sampling method, taking the location of the school into consideration. Descriptive statistics were used to examine the overall trends in school organisation culture. T-test was used to examine differences among research variables depending on the personal background of gender and teacher level, and the F-test and Scheffe tests were used for school level and teaching experience. Results. First, school's organization culture is transforming and evolving into a more ideal and model culture. As schools increasingly transform into innovative schools, innovative cultures and group cultures gradually form. Second, a school is a type of organization system that elicits responses elicits a variety of responses from the teachers depending on their personal background and characteristics. Third, professional learning communities have a positive effect on teacher efficacy. Therefore, school organisation culture can be seen as a better predictor of teacher ef ficacy than a professional learning community. Discussion and Conclusion. The article is of interest to the managers of the school educat ion system.